Refractory cutaneous Crohn's disease of the external genitalia in a female - Goyal, Pallavi (Indian J Sex Transm Dis AIDS, 2020)
Cutaneous lesions as a part of Crohn's disease (CD) may occur as a totally separate entity without the involvement of the gastrointestinal tract, in which case it is termed as metastatic CD. A 23-year-old female presented with complaints of vulvar swelling and multiple, oval-linear, typical knife cutting deep ulcers on the perineal folds. Biopsy showed epithelioid cell granuloma in the dermis. Differential diagnosis included cutaneous tuberculosis, sarcoidosis, deep fungal infection, and CD of the vulva. A diagnosis of CD was made by the exclusion. The patient was earlier treated with oral steroids, antibiotics, antituberculosis treatment, and azathioprine but showed only mild improvement. Therefore, the condition was regarded as a refractory one. The patient showed significant improvement after six cycles of adalimumab.